Christmas poems - Duffy, Carol Ann (London : Pan Macmillan, 2021)
This beautifully illustrated collection brings together, for the first time, Carol Ann Duffy s much-celebrated festive poems.
Includes indexes.
Keywords: Christmas poetry, -- English; Poetry